Elements of Nature in Cenap Şahabettin's Poem “Ta'yîn-i Metâlib" - Aytaç, Aslıhan (Fırat University, 2024)
Cenap Şahabettin, one of the artists of the Servet-i Fünûn period, is among the founders of modern Turkish poetry with his prioritization of aesthetic feeling, original discourse and original imagination system. Thanks to the aestheticized style he meticulously created in his poems, the poet had an important place in the history of Turkish literature, also by dipping into original subjects and themes. Cenap Şahabettin, who interprets the phenomenon of writing poetry as an existential dread, still to this day, continues to direct the literary formations after him with his poetic texts. As a poet bound to an aesthetic understanding, Cenap Şahabettin, who based his poems on the principle of beauty, creates a painting by integrating his impressions of nature with spiritual feeling and initiates the tendency to depict natural landscapes in Turkish literature. Nature is imagined as an ideal space for the poet, who is struggling with an ontic dilemma, reflecting his will to escape. Cenap Şahabettin, who identified the symbols of his spiritual life with the elements of nature, presented the natural principles of the Servet-i Fünûn period to the reader with his poem "Ta'yîn-i Metâlib". Cenap Şahabettin, who has introduced many innovations in Turkish poetry, used the elements of nature as a means of symbolization in "Ta'yîn-i Metâlib", while revealing his desires, wishes and expectations for the future with images unique to symbolists.

Servet-i Fünûn dönemi sanatkârlarından biri olan Cenap Şahabettin, estetik duyuş tarzını öncelemesi, benzersiz söylemi ve orijinal imgelem sistemiyle modern Türk şiirinin kurucuları arasında yer alır. Şair, şiirlerinde titizlikle meydana getirdiği estetize üslup biçiminin yanı sıra özgün konu ve temleri imgeleştirerek Türk edebiyatı tarihinde önemli bir yere sahip olur. Şiir yazma edimini, bir varoluş sorunu şeklinde anlamlandıran Cenap Şahabettin, poetik metinleriyle de kendisinden sonraki edebî oluşumları yönlendirmeye devam eder. Estetik anlayışa bağlı olarak şiirlerinde güzellik ilkesini esas alan Cenap Şahabettin, tabiata dair izlenimlerini tinsel duyuşla bütünleştirerek bir tablo görüntüsü meydana getirir ve Türk edebiyatında tabiat manzaralarını tasvir etme yönelimini başlatır. Tabiat, ontik çıkmazda bulunan şair için kaçış istencini yansıtan ideal bir mekân şeklinde imgeleştirilir. Ruhsal yaşantısına ait simgeleri, tabiat unsurlarıyla özdeşleştiren Cenap Şahabettin, Servet-i Fünûn dönemi tabiat ilkelerini “Ta’yîn-i Metâlib” isimli şiiriyle okuyucuya sunar. Türk şiirinde pek çok yeniliğe imzasını atan Cenap Şahabettin, “Ta’yîn-i Metâlib”de tabiat unsurlarını, sembolleştirme aracı şeklinde kullanırken geleceğe dönük arzu, istek ve beklentilerini sembolistlere özgü imajlarla ortaya koyar.
CENAP ŞAHABETTİN’İN “TA’YÎN-İ METÂLİB” ŞİİRİNDE TABİAT UNSURLARI
Keywords: Stylistics and Textual Analysis; Stilistik ve Metinsel Analiz